Metode Bernyanyi Terhadap Penanaman Karakter Anak Usia Dini - Usman, Nurmala; Herliina, Herlina; Herman, Herman; Wahira, Wahira; Darwis, Assidiq (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2026)
The singing approach is one of the most effective methods in early childhood learning. Singing is not only fun for children, but also has many developmental benefits, including language development, motor skills, social skills, and even cognitive skills. This study aims to determine the formation of moral values ​​in early childhood towards the instilling of children's character and to determine the supporting and inhibiting factors of the singing method towards the instilling of character in early childhood. This study uses a qualitative approach using three main techniques in data collection, namely interviews, observation, and documentation. Data analysis uses the approach proposed by Miles and Huberman (1994), which includes three main steps: data condensation, presenting data (data display), and drawing conclusions or verification (conclusion drawing and verification). The results of the study show that (1) the singing method is proven to be effective in forming moral values ​​and characters of honesty, discipline, caring, and cooperation in children aged 5-6 years through specific song lyrics, repetitive rhythms, and social interaction., (2) Supporting and inhibiting factors of the singing method towards the instilling of character in early childhood. Supporting factors dominate, with conducive classroom facilities, teacher-parent collaboration, and local lyrics increasing participation. While inhibiting factors include the heterogeneity of shy children, limited time (twice a week), and distractions from gadgets that lead to forgetting lyrics. This research serves as a model for early childhood education (PAUD) that can be replicated nationally, proving that the traditional art of singing effectively addresses the challenges of early childhood character education in the digital age by integrating local cultural preservation.